Interprofessional Collaboration - Dawn Prentice; Joyce Engel; Karyn Taplay; Karl Stobbe (SAGE Publishing, 2015)
In this hermeneutic phenomenological study, we examined the experience of interprofessional collaboration from the perspective of nursing and medical students. Seventeen medical and nursing students from two different universities participated in the study. We used guiding questions in face-to-face, conversational interviews to explore students' experience and expectations of interprofessional collaboration within learning situations. Three themes emerged from the data: the great divide, learning means content, and breaking the ice. The findings suggest that the experience of interprofessional collaboration within learning events is influenced by the natural clustering of shared interests among students. Furthermore, the carry-forward of impressions about physician-nurse relationships prior to the educational programs and during clinical placements dominate the formation of new relationships and acquisition of new knowledge about roles, which might have implications for future practice.